PENDAMPINGAN PSIKOLOGIS DAN HUKUM PADA ANAK KORBAN KEKERASAN SEKSUAL MELALUI ORGANISASI LEMBAGA KEMASLAHATAN KELURGA NAHDATUL ULAMA - Ulil Hidayah; Khasana Ilmi; Nova Zahriyah; Imro Atus Soliha; Agustiarini Eka Dheasari (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
This article discusses psychological and legal assistance for child victims of sexual violence through the Nahdlatul Ulama Family Welfare Institution (LKKNU). Psychological assistance includes early identification, emotional stabilization, therapy, and long-term monitoring, while legal assistance includes reporting, trial assistance, and protection of children's rights. With a multidisciplinary approach based on religious values ​​and local wisdom, LKKNU provides holistic support that focuses on recovery and justice for victims. This article recommends cross-sector collaboration to strengthen child protection from sexual violence.